An analysis of cost efficiency of Chinese Banking industry during the period of 2013-2017 - YIN, TAO (2018)
This paper adopts a stochastic frontier model to analyze the cost efficiency of Chinese banking sector during the period of 2013-2017. The unbalanced sample data contains 74 active commercial banks including state-owned commercial banks, joint-stock banks, city-commercial banks, rural-commercial banks and foreign-funded banks in China. By employing the Battese and Coelli (1995) model this paper also investigates the impact of macroeconomic environment factors including GDP growth rate, broad money growth, inflation and market concentration on cost efficiency. However, the results of all these macroeconomic environment variables showed insignificant influence on efficiency which also indicates that the macroeconomic environment of China during 2013-2017 is relatively stable. The average efficiency score in this period is 0.9629. By investigating the efficiency score in terms of ownership, we found that foreign-funded banks have the highest efficiency score among all bank types, then followed by join-stock banks. City-commercial banks stays at the bottom of the rank. State-owned commercial banks also remain in a relatively low efficiency level which is also consistent with the literature. Moving to the comparison of efficiency score in different regions, the middle reaches of Yellow River have the highest efficiency level. The coastal area seems to have a relatively higher average efficiency than the inland areas. The southwest, northeast and the great northwest regions have the lowest efficiency score. At the end, some policy implication is discussed.